Pengaruh Metode Pengeringan dan Jenis Sortimen Kayu Suren terhadap Kecepatan dan Cacat Pengeringan - Yustinus Suranto; Mugiyana Mugiyana (Fakultas Kehutanan Universitas Gadjah Mada, 2009)
Effect of Drying Method and Lumber Dimension on Drying Rate and Defects of Suren WoodEfforts to improve productivity of wood industry must be supported by increasing supply of wood as raw materials. The limited wood supply due to natural forest degradation can be increased by wood harvested from plantation forests, including wood of suren (Toona sureni Merr) as one species composing the forests. In timber processing wood drying is an important aspect determining product quality. This study aimed to identify the effect of drying method and sortimen dimension on drying character of suren wood.Trunks of 3 suren trees of seven to nine years old were cut from Manggihan village, Getasan district, Semarang regency. The bolts were sawn (using blambangan method) to obtain sortimen papan wood of 3 cm (thickness), 8 cm (width), and 210 cm (length) and sortiment usuk wood of 4 cm, 6 cm and 210 cm. Beside two levels of sortimen size, two levels of drying method, e.g. natural and solar drying were also used in this research. Resulted data were analyzed with factorial complete randomized design. Measured parameters consisted of drying rate, dimension shrinkage and some drying defects e.g. bowing, cupping, end check, surface check and fungi infection.Research results showed that drying methods significantly affect drying rate, but not other parameters. Also, product dimension affects significantly to drying rate, but not other parameters. Interactions between the two factors did not give any significant effect on all parameter. To produce the same drying level on the same product size, solar drying method is faster than natural one. To reach dry wood with 14% moisture content in solar drying method, sortimen papan and usuk needs 23 and 26.8 drying days respectively, while in natural drying method, the same product size needs 44.6 and 48.50 days of drying respectively.